Pengukuran Antropometri dan Penentuan Status Gizi Balita di Posyandu Balita Bina Sejahtera Kadipiro Banjarsari Surakarta - Dewi Marfuah; Siti Sarifah; Siti Khusnul Khotimah; Dhinda Kusuma Hatifah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The nutritional status of toddlers is an indicator of health status in Indonesia. Good nutritional status can help children's growth and development process to achieve optimal maturity. Nutritional status can help to detect the risk of health problems early. The role of posyandu is very necessary in efforts to prevent nutritional disorders in toddlers, so it is necessary to measure and determine the nutritional status of babies and toddlers. This community service aims to carry out anthropometric measurements of babies and toddlers and provide counseling to mothers of babies and toddlers about their children's nutritional status. This service activity is anthropometric measurements, namely weighing, measuring height or body length and Lila. Activities to determine nutritional status using WHO Antro. The results of measuring the nutritional status of BMI/U toddlers show that the majority of toddlers are in the normal category, 51 toddlers (80.96%), the nutritional status of BB/U toddlers shows that the majority are in the good (normal) category, 54 toddlers (85.71%). ), the nutritional status of PB/U or TB/U toddlers shows that the majority of toddlers are in the good (normal) category, amounting to 53 toddlers (84.13%), the nutritional status of BB/PB or BB/TB toddlers shows that the majority of toddlers are in the category good (normal) for 52 toddlers (82.55%). It is necessary to explain the results of anthropometric measurements to mothers of toddlers so that mothers of toddlers understand the nutritional status of their children and need to carry out nutritional education to prevent nutritional problems in babies and toddlers.